Resultado de partos domiciliares atendidos por enfermeiras de 2005 a 2009 em Florianópolis, SC - Koettker, Joyce Green; Brueggemann, Odalea Maria; Dufloth, Rozany Mucha [UNESP]; Knobel, Roxana; Monticelli, Marisa (Revista de Saúde Publica, 2012)
A cross-sectional study was performed to analyze obstetric and neonatal results of planned home births assisted by obstetric nurses in the city of Florianepolis, Southern Brazil. Data collected from the medical records of 100 parturient women cared for between 2005 and 2009 indicated 11 hospital transfers, nine of which underwent a Cesarean section. The majority of women who had a home birth showed normal fetal heart beat (94.0%) and progress on the partogram (61.0%), vertical water delivery was the position most frequently chosen (71.9%), newborns had an Apgar score >= 7 at five minutes (98.9%), episiotomy was performed in 1.0%, and 49.4% did not need perineal suturing. Outcomes indicated that planned home birth is safe.
Outcomes of planned home birth assisted by nurses, from 2005 to 2009, in Florianopolis, Southern Brazil
Keywords: Home Childbirth; Humanizing Delivery; Natural Childbirth; Nurse Midwives; Obstetrical Nursing